Deep learning approaches to predict late gadolinium enhancement and clinical outcomes in suspected cardiac sarcoidosis. - Azoulay, Levi-Dan; Mei, Xueyan; Fauveau, Valentin; Liu, Zelong; Robson, Philip; Levi, Sydney; Devesa, Ana; Trivieri, Maria-Giovanna; Fayad, Zahi (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2025)
-